Public Safety Challenges Faced by Barangay Officers and Police: Towards a Stronger Policy Framework - Villafuerte, Arvin (Journal of Interdisciplinary Perspectives, 2024)
This study examines public safety challenges and collaboration between Barangay Public Safety Officers and the National Capital Region Police Office (NCRPO), aiming to enhance police-community partnerships and strengthen public safety measures in the National Capital Region. Using a descriptive- correlational research design, data were collected from 45 barangay public safety officers and 45 NCRPO police officers through questionnaires. The study explored correlations between identified challenges and the effectiveness of public safety measures to propose an improved policy framework. Findings reveal high effectiveness in current public safety measures, supported by excellent police service delivery, strong local executive backing, and robust community partnerships. Respondents, predominantly middle-aged male college graduates, consistently perceived public safety measures positively across demographic categories. However, critical challenges persist in community engagement, organizational support, and policing strategies, reflecting systemic issues common to other regions and departments. A perfect linear correlation was found between these challenges and the effectiveness of public safety measures, underscoring their direct impact on overall performance. The study emphasizes addressing these challenges to enhance public safety outcomes and foster stronger police-community collaborations, providing valuable insights for policy improvements in the NCR.